PERLINDUNGAN HUKUM BAGI NASABAH PEMILIK ANJUNGAN TUNAI MANDIRI(ATM) SEBAGAI KORBAN TINDAK PIDANA SKIMMIN - Siregar, Desy Yurita; Christiawan, Rio; Saputera, Januar Agung (Universitas Islam Sumatera Utara, 2024)
As a business practice, banks play an important role in collecting money from the public in the form of deposits, and channeling it into the form of credit or other forms, so that, banks aim to improve the standard of living of the people or the economy of a country. . Automated Teller Machines (ATMs) are one of the items that have emerged from technology in the banking sector that can facilitate transaction activities without the need to visit bank tellers due to advances in the times and technology. The development of a technology can have a positive impact and a detrimental impact, one of which is the emergence of cybercrime (Cyber Crime) in the banking world which is commonly referred to as skimmingcrimes. The type of normative legal research is used as research on the rule of law, the level of norms, principles, philosophies, theories and the rule of law itself, with an approach to legislation (Statute Approach). Then the purpose of this study is to find out how to protect the law for customers who own automated teller machines (ATMs) who experience skimming crimes and how to apply sanctions against perpetrators for skimming crimes on automated teller machines (ATMs), so that it can be concluded that every criminal act in skimming crimes may be sentenced to criminal sanctions and administrative sanctions for those who are proven to have done so.therefore the application of criminal sanctions used in the crime of skimming is contained in article 30 paragraph (2) jo 46 paragraph (2) of Law Number 11 of 2008 which has been amended into Law No. 19 of 2016 jo article 55 paragraph (1) 1 of the Criminal Code jo article 363 of the Criminal Code Keywords: Skimming, Legal Protection, Application of Criminal Sanctions